The Role of Volatile Organic Compounds and Rhizosphere Competence in Mode of Action of the Non-pathogenic Fusarium oxysporum FO12 Toward Verticillium Wilt - Mulero-Aparicio, Antonio; Cernava, Tomislav; Turrà, David; Schaefer, Angelika; Di Pietro, Antonio; López-Escudero, Francisco Javier; Trapero, Antonio; Berg, Gabriele (Frontiers in Microbiology, 2019)
Verticillium wilts caused by Verticillium spp. are among the most challenging plant diseases to control and affect numerous hosts worldwide. Due to the lack of effective, conventional control methods, integrated control strategies provide a promising approach to manage these diseases. The non-pathogenic Fusarium oxysporum strain FO12 was reported in previous studies to be an effective biocontrol agent against Verticillium dahliae, however its mode of action remains to be elucidated. In this study, complementary in vitro and in vivo experiments were conducted in order to explore the implications of inhibitory substances and rhizosphere competence in antagonistic effects of FO12 against V. dahliae and V. longisporum. Volatile organic compounds and soluble substances produced by FO12, which caused significant inhibition of mycelial growth and microsclerotia viability in the two tested Verticillium species, were identified by means of gas and liquid chromatography-mass spectrometry. We showed that the antagonistic effect of F. oxysporum FO12 is partially due to the production of bioactive compounds such as 3-methyl-1-butanol and 2-methyl-1-butanol, among others. Several metabolic pathways of FO12 were altered upon contact with V. dahliae ELV22 volatiles. The reduced production of alpha, alpha-trehalose, a metabolite used in starch and sucrose metabolism, suggests that the biocontrol agent activates its stress response in the presence of the phytopathogen. Microscopic analysis using sGFP-tagged FO12 on oil seed rape as a model plant suggests that the biocontrol strain is an efficient root colonizer, which could competes with V. dahliae in the same ecological niche. The findings obtained in this study provide new insights into the mode of action of this potential biocontrol agent, which are relevant for controlling Verticillium wilt through an ecologically friendly approach.